Predicting Women\'s Sexual Function Based on Circadian Rhythms and Anxiety Sensitivity - Ameneh Dashtestannejad; Akram Dehghani; Azam Salehi; Mohammad Massoud Dayarian (Zanjan University of Medical Sciences and Health Services, 2021)
Background: Sexual dysfunction is one of the factors causing adverse effects on marital life. Objectives: Therefore, the present study aimed at predicting female sexual function based on circadian rhythms and anxiety sensitivity. Methods: The present descriptive-correlational study was performed on 378 married women referring to cultural centers in Isfahan, Iran, from September 2019 to March 2020. The multistage cluster and then convenience sampling methods were used to select samples. Data collection instruments included the female sexual function index developed by Rosen et al., morningness-eveningness personality questionnaire designed by Horne and Ostberg, and anxiety sensitivity index developed by Floyd et al. The collected data were analyzed using Pearson correlation coefficient and stepwise regression with SPSS version 24. Results:: The means of age and marriage years of the study participants were 32.53±7.74 and 7.09±3.76 years, respectively. The mean score of their sexual function was 56.85±12.65 and the circadian rhythm 40.84±11.57, and the overall score of anxiety sensitivity 44.99±7.19. The findings also showed that the relationship between sexual function and circadian rhythms was 0.17 and anxiety sensitivity -0.18 (P<0.01). The relationship between sexual function and the components of anxiety-related physical sensations, cognitive dyscontrol, and fear of publicly observable anxiety was -0.14, -0.13, and -0.11, respectively (P<0.05). In the first stage, anxiety sensitivity could predict 16.7% of changes in sexual function and circadian rhythms 7.1% of the mean changes in sexual function (P<0.001), so it can be said that anxiety sensitivity and morningness personality could predict 24% of sexual dysfunction variation (P<0.001).Conclusion: The present study findings show that anxiety sensitivity and circadian rhythms are among the factors affecting sexual function; therefore, it is recommended to reduce anxiety and improve sleep quality to treat sexual disorders in married women.